CP-066 Appreciation of reduction of drug prices by policyholders of health insurance and its impact on access to drugs. (25th February 2017) - Cheikh, A; Zegraoui, S; Bouatia, M; Cherrah, Y; Nadif, M; Hassani, A El
Abstract : Background: Drug prices are the main obstacle for the majority of the population without a health insurance regimen. A reduction in drug prices is an important regulation tool to improve access to drugs for patients. Sometimes this reduction is not well perceived by patients, in particular when they cannot advance the cost of purchasing their medication and be reimbursed later by their health insurance company. Purpose: Throughout this work, we wanted to evaluate patient satisfaction regarding reduction of drug prices by the Ministry of Health. We wanted to study factors that influence patients' appreciation of reduction in drug prices. Material and methods: A questionnaire was given to patients admitted to our hospital and affiliated with mandatory health insurance. The goal was to find out whether these price reductions were appreciated by patients and helped to improve their financial accessibility to drugs. A univariate and multivariate analysis was used to examine the factors that influence patients' appreciation of a reduction in prices. Statistical analysis was done with SPSS 13.0. Results: 200 questionnaires were distributed over a 6 month period; 130 were completed correctly. Men represented 69% and married patients comprised 56%. 41% had private health insurance and the rest(59%) had public insurance. 28% were not satisfied, 37% did not feel the impact and 20% were satisfied with the reduction in prices. 6% were very unsatisfied and 9% were very satisfied. The patients' sex and income significantly influenced their appreciation of the reduction in drug prices (p=0.042 and p=0.049). Education level, type of health insurance (public, private) and the remaining costs beyond the insured part did not influence their appreciation of the reduction in prices (p>0.05). Conclusion: 71% of patients were not satisfied or had not felt the impact of the reduction in drug prices on their accessibility to drugs. The reduction in drug prices did not have the desirable effect if patients had to pay for their drugs and be reimbursed later. A system of direct payment between the insurance provider and pharmacies to cover drugs costs would be more appreciated than a simple reduction in medicine prices. References and/or acknowledgements: Acknowledgements to policyholders who responded to us. No conflict of interest